High-salt–fat diet: a risk factor for elevated blood pressure associated with dyslipidemia, perturbation in cardio-renal anti-oxidant and pro-inflammatory status in Wistar rats - Olumide Samuel Fadahunsi; Olubukola Sinbad Olorunnisola (Journal of Basic and Applied Zoology)
Abstract Background Fatty and salty diets are reported risk factors in the etiology of hypertension, renal and cardiac failure. Oxidative stress and inflammation are biochemical processes in the onset of most diseases. This study sought to evaluate the role of high-salt–fat diet (HS-HFD) on blood pressure (BP), cardio-renal function, redox and inflammatory status. Twelve male Wistar rats were divided into two groups and fed with normal chow and HS-HFD, respectively. Results After 12 weeks, HS-HFD-fed rats showed considerable weight reduction, elevated systolic and diastolic BP. Serum cholesterol and low-density lipoprotein (LDL) were increased, and high-density lipoprotein (HDL) and triacylglycerol levels were significantly (p < 0.05) reduced in the HS-HFD-fed animals. Angiotensin 1-converting enzyme was elevated in the HS-HFD rats, with no difference in nitric oxide between the two groups. Urea, lactate dehydrogenase, creatinine, bicarbonate and chloride levels were elevated in the HS-HFD-fed group, while potassium, sodium and magnesium were reduced. Creatine kinase activity was reduced in the heart of HS-HFD rats, with no difference in serum troponin. The kidney of HS-HFD rats showed increased superoxide dismutase (SOD), glutathione peroxidase, glutathione and glutathione-S-transferase (GST) with reduced catalase and malondialdehyde (MDA). Heart SOD, catalase and MDA levels were similar in the two groups, with GPx, GST and GSH elevated in the control. Kidney tumor necrosis factor-α (TNF-α) increased in HS-HFD group, with no difference in the heart of the rats in the two groups. TGF-β decreased in the kidney and heart of the HS-HFD-fed rats. Conclusions HS-HFD elicited hypertension associated with perturbation in redox and pro-inflammatory status in the kidney and heart of the rats.